An equivalent pseudo spectral method for estimating fatigue damage under two Gaussian random loads. (1st April 2020) - Han, Chaoshuai; Ma, Yongliang; Xing, Junhua; Zhang, Zhongyu; Liu, Kun
Abstract: Most marine structures are commonly subjected to two various random loads. Two dynamic responses are generally performed in two different domains (time domain or frequency domain) separately. The induced stress responses may be a combination of two stress time series or a combination of a stress time series and a stress spectrum or a combination of two stress spectra. Fatigue damage can be predicted through different methods. Non-linear time domain method is accurate but time-consuming. The classical frequency domain method is convenient only for the third combination case but is limited for the first two combination case since some spectral parameters are not easily available. This paper proposes an equivalent pseudo spectral method to evaluate fatigue damage under the first two combination case. The new method is proven to be an efficient alternative approach that avoids the cumbersome procedure of simulation and cycle counting. The reliability of the new method is first demonstrated by a sensitivity study that the effect of spectral shape on fatigue damage and bandwidth parameter. Then accuracy of the new method is second verified by comparing fatigue damages from various models with rainflow fatigue damages which is obtained from equivalent triangular bimodal stress spectra. Highlights: The bandwidth parameters are insensitive to the geometric shapes of stress PSDs. Fatigue damage is insensitive to the geometric shapes of stress PSDs. Separated and overlapped triangular spectra are constructed to predict fatigue damage which provides very precise results.